2005
DOI: 10.1140/epjc/s2005-02277-x
|View full text |Cite
|
Sign up to set email alerts
|

2PI effective action and gauge dependence identities

Abstract: The problem of maintaining gauge invariance when truncating the two particle irreducible (2PI) effective action has been studied recently by several authors. Here we give a simple and very general derivation of the gauge dependence identities for the off-shell 2PI effective action. We consider the case where the gauge is fixed by an arbitrary function of the quantum gauge field, subject only to the restriction that the Faddeev-Popov matrix is invertable. We also study the background field gauge. We address the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 13 publications
0
67
0
1
Order By: Relevance
“…Given the manifestation of the phase transition in the correlation functions, it is an interesting question whether also the other thermodynamic information can be obtained from the correlation functions. Indeed, it is, in principle, possible to determine the thermodynamic potential by a 2PI/Luttinger-Ward-Cornwall-Jackiw-Tomboulis construction [239,280,[446][447][448][449][450][451][452]. The exact expression is given by [452] …”
Section: Ghost Schwinger Function In Four Dimensionsmentioning
confidence: 99%
“…Given the manifestation of the phase transition in the correlation functions, it is an interesting question whether also the other thermodynamic information can be obtained from the correlation functions. Indeed, it is, in principle, possible to determine the thermodynamic potential by a 2PI/Luttinger-Ward-Cornwall-Jackiw-Tomboulis construction [239,280,[446][447][448][449][450][451][452]. The exact expression is given by [452] …”
Section: Ghost Schwinger Function In Four Dimensionsmentioning
confidence: 99%
“…One is that it is straightforward to systematically extend the order of the approximation. Another is that the truncation respects the symmetries of the original theory, to the order of the approximation [21,22]. To solve the flow equations, one chooses μ large enough that when κ = μ the theory is classical and the 2-and 4-point functions are known functions of the bare parameters.…”
Section: -P4mentioning
confidence: 99%
“…Equation (22) gives a series of infinite hierarchies of coupled equations for the 2PI kernels in which kernels with fixed n and different m are coupled together. However, unlike the hierarchy produced from the 1PI effective action, when the 2PI effective action is truncated at some finite loop order, the hierarchy in (22) is also truncated.…”
Section: -P4mentioning
confidence: 99%
“…This situation is reminiscent of the recent proof that the truncated on-shell 2PI effective action has a controlled gauge dependence, with the explicit gauge-dependent terms always appearing at higher order [11][12][13].…”
Section: Gauge Dependence Of the Fermion Quasiparticle Polesmentioning
confidence: 99%
“…While the position of quasiparticle poles in the leading order HTL approximation are completely gauge independent [9,10], nevertheless gauge dependence will enter at subleading order and gauge-independent extensions beyond the leading order HTL results are not yet available. More recently, several authors [11][12][13] have shown that the truncated on-shell two-particle-irreducible (2PI) effective action has a controlled gauge dependence, with the explicit gauge-dependent terms always appearing at higher order. It would be interesting to study possible cancellation of the leading gauge dependence in the singularity structure of gauge boson and fermion propagators beyond the * Current Address: Department of Physics and Astronomy, University of Delaware, Newark, Delaware 19716, USA; Electronic address: sywang@physics.udel.edu leading order HTL approximation.…”
Section: Introductionmentioning
confidence: 99%